2004
DOI: 10.1002/jmv.20074
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of double‐stranded RNA‐activated protein kinase in hepatocellular carcinoma associated with hepatitis B virus

Abstract: Chronic hepatitis B virus (HBV) infection is a major cause of hepatocellular carcinoma (HCC) in Asia. Double-stranded RNA (dsRNA)-activated protein kinase (PKR) is an interferon-induced, serine/threonine protein kinase. Recent studies have suggested that PKR is involved in the pathogenesis of HCC with hepatitis virus C infection by inhibiting viral and cellular proteins related to cell growth and proliferation. In the present study, PKR was examined in both tumor and non-tumor tissues from HCC livers infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…PKR activation is not sufficient to cause cell death because of the strong anti-apoptotic signalling in HCV infected cells [16]. Our work showed no significant difference in expression of PKR among patients with well differentiated tumours and those with poor or moderate differentiation, this is in concordance with other study [34]. While a previous report showed that the expression of PKR was increased significantly in well-differentiated HCC related HBV infection, compared with that in poorly differentiated HCC [36].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…PKR activation is not sufficient to cause cell death because of the strong anti-apoptotic signalling in HCV infected cells [16]. Our work showed no significant difference in expression of PKR among patients with well differentiated tumours and those with poor or moderate differentiation, this is in concordance with other study [34]. While a previous report showed that the expression of PKR was increased significantly in well-differentiated HCC related HBV infection, compared with that in poorly differentiated HCC [36].…”
Section: Discussionsupporting
confidence: 92%
“…Thus HCV core protein may induce a shift of PKR activity from its classical pathway by targeting other substrates [14,33]. Chen and his colleagues found that PKR level was much reduced in HCC than that in non-tumour tissues [34]. This is not surprising, as PKR is considered a tumour suppressor in some cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…A good example might be that of Hepatitis B Virus (HBV) [36], [37], [38]. PKR expression was previously reported to be elevated in HCC liver from chronically HBV infected patients [39] and a relationship between PKR and IFN induction during HBV infection would be important to evaluate.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to interferon-inducible genes with antiviral activity, several genes known or predicted to possess growth-inhibition and/or cell-differentiating activities [49,50] were induced by imiquimod, including IFI16 , AIM2 [62,63], IFIH1 (melanoma differentiation antigen, MDA5 ) [45], CXCL10 ( IP10 ) [58] and EIF2AK2 (PRKR ) [64]. Some of the interferon-inducible genes also possess pro-apoptotic activity, including MX1 , TNFSF10 ( TRAIL ), OAS1 , and PRF1 [55,57,65].…”
Section: Resultsmentioning
confidence: 99%